Integrated Reporting And Firm Performance In Malaysia: The Moderating Effect Of Board Diversity And Family Ownership - Lok, Yee Huei (2023)
This study examines the relationship between integrated reporting disclosures and firm performance in the context of listed companies in the main market of Bursa Malaysia. This study also includes moderating variables namely, board gender diversity, board age diversity, and family ownership to further examine the relationship between integrated reporting disclosures and firm performance.